Optimalisasi Komunikasi Pemerintah Daerah oleh BPBD dalam Penanganan Risiko Banjir di Kabupaten Tulungagung (Jurnal Riset Rumpun Ilmu Sosial, Politik dan Humaniora, 2026)
Flood disasters are recurring hydrometeorological hazards that significantly impact social, economic, and environmental conditions in Tulungagung Regency. This study aims to analyze the flood disaster mitigation communication strategies implemented by the Regional Disaster Management Agency (BPBD) of Tulungagung Regency and to identify the roles, challenges, and implications of both internal and external communication in flood disaster management. The research employed a qualitative approach using a descriptive method. Data were collected through in-depth interviews with the Secretary of BPBD Tulungagung Regency, the Head of the Emergency and Logistics Division, the Head of the Prevention and Preparedness Division, and members of flood-affected communities. The findings reveal that BPBD Tulungagung Regency has attempted to optimize disaster communication during the pre-disaster, emergency response, and post-disaster phases. The effectiveness of these communication efforts remains limited due to several challenges, including inadequate communication infrastructure, varying levels of disaster literacy among community members, diverse geographical conditions, and insufficient coordination in internal and external communication. Pre-disaster communication plays an essential role in improving community preparedness, communication during emergency response supports timely and accurate decision-making, and post-disaster communication contributes to recovery processes and the strengthening of community resilience. This study concludes that optimizing disaster communication requires integrated information systems, improved human resource capacity within BPBD, and active community participation through community-based communication approaches to sustainably enhance resilience to flood risks.